Determine whether the improper integral converges or diverges, and find the value of each that converges.∫^0_-[infinity] 5e^60x dx

Answers

Answer 1
Answer:

Answer:

The improper integral converges.

\displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = (1)/(12)

General Formulas and Concepts:
Calculus

Limit

Limit Rule [Variable Direct Substitution]:                                                         \displaystyle \lim_(x \to c) x = c

Differentiation

  • Derivatives
  • Derivative Notation

Derivative Property [Multiplied Constant]:                                                       \displaystyle (d)/(dx) [cf(x)] = c \cdot f'(x)

Derivative Rule [Basic Power Rule]:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Integration

  • Integrals

Integration Rule [Reverse Power Rule]:                                                           \displaystyle \int {x^n} \, dx = (x^(n + 1))/(n + 1) + C

Integration Rule [Fundamental Theorem of Calculus 1]:                                 \displaystyle \int\limits^b_a {f(x)} \, dx = F(b) - F(a)

Integration Property [Multiplied Constant]:                                                     \displaystyle \int {cf(x)} \, dx = c \int {f(x)} \, dx

Integration Method: U-Substitution

Improper Integral:                                                                                             \displaystyle \int\limits^(\infty)_a {f(x)} \, dx = \lim_(b \to \infty) \int\limits^b_a {f(x)} \, dx

Step-by-step explanation:

Step 1: Define

Identify.

\displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx

Step 2: Integrate Pt. 1

  1. [Integral] Rewrite [Integration Property - Multiplied Constant]:             \displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = 5 \int\limits^0_(- \infty) {e^(60x)} \, dx
  2. [Integral] Rewrite [Improper Integral]:                                                     \displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = \lim_(a \to - \infty) 5 \int\limits^0_(a) {e^(60x)} \, dx

Step 3: Integrate Pt. 2

Identify variables for u-substitution.

  1. Set u:                                                                                                         \displaystyle u = 60x
  2. [u] Differentiate [Derivative Properties and Rules]:                                 \displaystyle du = 60 \ dx
  3. [Bounds] Swap:                                                                                         \displaystyle \left \{ {{x = 0 \rightarrow u = 0} \atop {x = a \rightarrow u = 60a}} \right.

Step 4: Integrate Pt. 3

  1. [Integral] Rewrite [Integration Property - Multiplied Constant]:             \displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = \lim_(a \to - \infty) (1)/(12) \int\limits^0_(a) {60e^(60x)} \, dx
  2. [Integral] Apply Integration Method [U-Substitution]:                             \displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = \lim_(a \to - \infty) (1)/(12) \int\limits^0_(60a) {e^(u)} \, du
  3. [Integral] Apply Exponential Integration:                                                 \displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = \lim_(a \to - \infty) (1)/(12) e^u \bigg| \limits^0_(60a)
  4. Evaluate [Integration Rule - Fundamental Theorem of Calculus 1]:       \displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = \lim_(a \to - \infty) (1 - e^(60a))/(12)
  5. [Limit] Evaluate [Limit Rule - Variable Direct Substitution]:                     \displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = (1 - e^(60(-\infty)))/(12)
  6. Rewrite:                                                                                                     \displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = (1)/(12) - (1)/(12e^(60(\infty)))
  7. Simplify:                                                                                                     \displaystyle \int\limits^0_(- \infty) {5e^(60x)} \, dx = (1)/(12)

∴ the improper integral equals\displaystyle \bold{(1)/(12)}  and is convergent.

---

Learn more about improper integrals: brainly.com/question/14413972

Learn more about calculus: brainly.com/question/23558817

---

Topic: AP Calculus BC (Calculus I + II)

Unit: Integration

Answer 2
Answer:

Answer:

\int_(-\infty)^0 5 e^(60x) dx = (1)/(12)[e^0 -0]= (1)/(12)  

Step-by-step explanation:

Assuming this integral:

\int_(-\infty)^0 5 e^(60x) dx

We can do this as the first step:

5 \int_(-\infty)^0 e^(60x) dx

Now we can solve the integral and we got:

5 (e^(60x))/(60) \Big|_(-\infty)^0

\int_(-\infty)^0 5 e^(60x) dx = (e^(60x))/(12)\Big|_(-\infty)^0 = (1)/(12) [e^(60*0) -e^(-\infty)]

\int_(-\infty)^0 5 e^(60x) dx = (1)/(12)[e^0 -0]= (1)/(12)  

So then we see that the integral on this case converges amd the values is 1/12 on this case.


Related Questions

What are the coordinates of the vertices of the image after a 90-degree counter-clockwise rotation about the origin? (2,3) (-3,-1) (2, -1)
Simplify 3-8 divided by 3-2
P (-5, -6), Q (-1, 2), R (4, 4)Scale factor = 2P' =Q' =R' =
the gas tank on toms car holds 20 gallons of gas. The fuel gauge of her car shows that the tank is 3/4 full. How many gallons of gas are in the gas tank?
Answer the following true or false. Justify your answer.(a) If A is a subset of B, and x∈B, then x∈A.(b) The set {(x,y) ∈ R2 | x > 0 and x < 0} is empty.(c) If A and B are square matrices, then AB is also square.(d) A and B are subsets of a set S, then A∩B and A∪B are also subsets of S.(e) For a matrix A, we define A^2 = AA.

What is the value of “a” in the function equation?

Answers

Answer:     the value of A is 2

Step-by-step explanation:

Ac and bd are perpendicular bisectors of each other. adc. Find eab

Answers

Let ∠ ADC = 2β

Ac and BD are perpendicular bisectors of each other ⇒⇒ (Given information)

∴ BD
bisects the angle ADC
∴ ∠ADE = 0.5 ∠ADC = β

And in ΔADE:
∵∠DEA = 90°    ⇒⇒⇒ from the given information
∴∠DAE = 90° - β

And AC bisects ∠DAB 
⇒⇒⇒ from the given information
∴∠EAB = ∠DAE = 90° - β

<EAB = 180 - 90 - (0.5*<ADC)

Perform the following calculation: (+10) + (–45). A. 55 B. –55 C. –35 D. 35

Answers

Answer:

Option C - (+10) + (-45)=-35

Step-by-step explanation:

Given : Expression (+10) + (-45)

To find : Perform the calculation in the given expression ?

Solution :

Step 1 - Write the expression

=(+10) + (-45)

Step 2 - Applying multiplication symbol rule,(+)(-)=(-)

=10-45

Step 3 - Solve the subtraction,

=-35

Therefore, Option C is correct (+10) + (-45)=-35

80 plus what equals 44??

Answers

Answer:

-36

Step-by-step explanation:

80 + (-36) = 44

The negative in the 36 allows it to be subtracted from 80

Answer:

80 + -36

Step-by-step explanation:

80 - 44 = 36

80 + -36 = 44

Hi I need help with the one that is circle thank you

Answers

Answer:

B1: +6 (to get to plus six you would have to pass negative one so really it's seven)

B2: they are the same distance

B3: -7

B4: +7  

<3 have a good day :)

Step-by-step explanation:

Answer:

hope this helped! Can I get brainliest? :)) please?

Step-by-step explanation:

1. +6 is the answer because it is 8 units away from -2

2.  both are the same distance from -2

3.  -7 is the answer because it is 5 units away from -2

4. +7 is the answer because it is 9 units away from -2

9. What is the value
of the expression?
21.3 + (-34.87)

Answers

Answer:

-13.57

Step-by-step explanation:

21.3 + (-34.87) = -13.57

Mark me as brainliest if you want to.